Asimetri Informasi dan Moral Hazard dalam E-Commerce: A Systematic Literature Review dalam Perspektif Ekonomi Islam - Hagi Andhika; Fakhri Ahmad Zainunnuri; Sri Rokhlinasari; Alvien Septian Haerisma (Insitut Pesantren Babakan cirebon, 2026)
This study aims to analyze the phenomena of information asymmetry and moral hazard in e-commerce through a Systematic Literature Review (SLR) approach from an Islamic economics perspective. The rapid growth of e-commerce, particularly social commerce, has increased consumers’ reliance on digital information such as ratings, reviews, and product reputation, which do not always reflect actual product quality. This condition leads to information asymmetry between sellers and buyers and creates opportunities for moral hazard behavior, including the manipulation of reviews, ratings, and product information. This research employs a qualitative method using an SLR approach based on the PRISMA framework to select relevant literature published between 2021 and 2025. The data are analyzed using thematic analysis to identify keythemes related to information asymmetry, moral hazard, their impact on consumer behavior and market efficiency, and the perspective of Islamic economics. The findings indicate that information asymmetry is the primary factor causing market distortion, while moral hazard emerges as a consequence of weak transparency and monitoring in digital systems. These phenomena contribute to decreased consumer trust, distorted perceptions of product quality, and market inefficiency. From an Islamic economics perspective, such practices contradict the principles of honesty, transparency, and fairness, and can be categorized as forms of gharar (uncertainty) and tadlis (fraudulent misrepresentation). This study concludes that integrating conventional economic approaches with Islamic economic principles is essential to develop a digital ecosystem that is not only efficient but also just and sustainable. Keywords: Information Asymmetry, Moral Hazard, E-Commerce, Islamic Economics, Systematic Literature Review